Berbagi Pengetahuan dan Efektivitas Kepemimpinan terhadap Kinerja Melalui Perilaku Kerja sebagai Pemediasi - Lufni Maidesi (Journal of Business and Economics (JBE) UPI YPTK, 2022)
This study aims to determine the effect of knowledge sharing and leadership effectiveness on performance through work behavior as an intervening variable at the West Pasaman Health Office. The method used is multiple linear regression analysis and path analysis. by distributing questionnaires as many as 83 respondents. The results obtained that there is a positive and significant influence of knowledge sharing on work behavior at the West Pasaman Health Office. There is a positive and significant effect of leadership effectiveness on work behavior at the West Pasaman Health Office. There is a positive and significant effect of knowledge sharing on the performance of the West Pasaman Health Office. There is a positive and significant effect of leadership effectiveness on performance at the West Pasaman Health Office. There is a positive and significant effect of work behavior on performance at the West Pasaman Health Office. Work behavior mediates the effect of knowledge sharing on performance. Work behavior mediates the effect of leadership effectiveness on performance. Finally, the authors suggest to the West Pasaman Health Office to further increase knowledge sharing, leadership effectiveness and work behavior so that employee performance is expected to increase.